Educação das relações étnico-raciais e decolonialidade na formação de professoras (es) de ciências naturais: reflexões sobre identidade étnico-racial, direitos humanos e ensino - Coelho, Pollyana Santos (2020)
The objective of this dissertation study, based on the undertaking of a Qualitative Metasynthesis, developed along the theoretical lines coined by its main Brazilian disseminators, the PhDs in Nursing: Ana Lúcia Mendes Lopes, Lislaine Aparecida Fracolli and Maria Clara Cassuli Matheus, to analyze the conformation of the specialized literature, which deals with the thematic association - Science Teacher Education, Science Teaching, Education of EthnicRacial Relations and Decolonial Thought - published in the Brazilian Digital Library of Theses and Dissertations (BDTD), in the period between the years 2003 to 2019, which marks sixteen years in force of Law N.º 10.639 / 2003. Using as instruments of comparative analysis and data treatment, respectively, the comprehensive hermeneutic reflection proposed by Hans-George Gadamer and the Textual Discursive Analysis (DTA) proposed by Roque Moraes and Maria do Carmo Galiazzi. In this sense, to achieve this purpose, we followed a theoreticalmethodological path based on the epistemological references of Escrevivência, Decolonial Thought, Decolonial Pedagogies and Critical Interculturality, based on the Afrocentric research worldview. Defending that, being Science and curricula instruments of power, hegemonic and homogenizing, vehicles and means of maintaining the Eurocentric colonialist logic, they serve and remount a dominant ideology of power resulting from colonialism, which even after the end of the colonization era, it has endured through the colonialities of: power, being, knowing, living and cosmogonic. Thus intending to contribute to the shy and emerging movement of unveiling, optics and other ways to, respectively, understand and develop Education in Natural Sciences, in an ethnic-racial and cultural perspective, which starts from the (re) knowledge and consideration of the role that it assumes, both in the production of racism and social injustices, and in its fight and promotion of anti-racism. In summary, the results show that: little has been considered the role assumed by Education, in general, and by Science Education, in particular, both in the production and in the fight against racism and other social injustices; academic production related to Teacher Education is scarce within the spectrum of themes related to ethnic-cultural and racial diversity, especially in the specific field of Natural Sciences; and that Science Education has been an effective instrument for the production and maintenance of social injustices, while it has served as a way of denying subjectivities, silencing of knowledge and knowledge, legitimizing processes of inferiorization of certain ethnic groups, black, hiding behind a racist propaganda, subtle of neutrality.